PREPARATION OF CALCIUM PHOSPHATE BIOCERAMIC POWDERS SYNTHESIZED IN SIMULATED BODY FLUID MEDIA - Bambang Sunendar -; Weko Abhinimpuno - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2009)
In this study, calcium phosphate bioceramics powders were synthesized using Ca(NO3)2.4H2O and (NH4)2HPO4 as the precursor by a biomimetic process. The condition of the synthesizing process is set mimicking the human physiological environment. The synthesized samples then were dried and calcined at several temperatures. The samples were studied after characterized by XRD, FT-IR, EDS and SEM. The process in this study was successful in synthesizing various types of calcium phosphate bioceramics.Keywords: Calcium phosphate bioceramics, biomimetic process